Activation of Chlorite with Sunlight for the Efficient Disinfection of Antibiotic-Resistant Bacteria: the Overlooked Contribution of Cytomembrane-Bound Chlorite - Yutao Shen; Fuyang Liu; Jialiang Liang; Li, Zhengmao; Hou, Yanghui; Jingfeng Wu; Yong Ting; Guo, Renjie; Yong Liu; Peng Han; Meiping Tong (Environmental Science & Technology, 2025)
Current antibiotic-resistant bacteria (ARB) disinfection techniques commonly rely on large dosages of oxidants, resulting in the presence of considerable amounts of residuals and toxic disinfection byproducts (DBPs) in water. Herein, we propose a highly effective ARB disinfection approach via activating an ultralow concentration (10 μM) of chlorite (ClO2–) by naturally abundant sunlight to generate various reactive species (i.e., HO•, Cl•, ClO•, and ClO2) with negligible generation of halogenated DBPs. Combining in situ characterization with theoretical calculations, we reveal that, in addition to the photolysis of ClO2– in the bulk solution, ClO2– ions electrostatically adsorbed on the positive local sites of lipids can boost light absorption and facilitate the in situ generation of reactive species upon sunlight irradiation, enabling more efficient attacks toward cell membranes and the intracellular antioxidant enzyme system. The intracellular antibiotic resistance genes (ARGs) are then released and further degraded, inhibiting horizontal ARG transfer. This approach can also achieve excellent ARB disinfection performance in real water matrices (e.g., lake and river water) in 1 L tanks and 500 mL plastic bottles with natural sunlight irradiation. Overall, this work presents an efficient, safe, and sustainable method to inactivate ARB with deep insights into disinfection mechanisms at the subcellular level.